Posterior Reversible Encephalopathy (PRES) in a Child with Severe Dengue. (9th September 2019) - Sawant, Yogini; Birajdar, Suresh; Doshi, Hiren; Soni, Pooja; Patkar, Deepak; Joshi, Narayan C
Abstract: Among neurological complications associated with dengue, posterior reversible encephalopathy syndrome (PRES) has not been reported in pediatric population. We report a 10-year-old girl with severe dengue who developed PRES. The patient presented with hemorrhagic shock that required fluid resuscitation and inotropic support. She developed seizures with encephalopathy 2 days after recovering from the shock. Cerebrospinal fluid (CSF) examination was negative for dengue (no white blood cells in CSF with negative polymerase chain reaction for dengue). Her clinical features and magnetic resonance imaging (MRI) findings showed typical changes associated with posterior encephalopathy that reverted after resolution of hypertension. Repeat MRI after a month was normal. PRES should be considered as a possible differential diagnoses of dengue associated encephalopathy, especially in cases with normal CSF examination and characteristic MRI changes.